Divergence in governance compliance between earning and non-earning manipulating firms and adherence deficiency: an analysis of Bursa Malaysia's public listed companies / Mohamad Ezrien Mohamad Kamal, Mohd Fairuz Md Salleh and Azlina Ahmad - Mohamad Kamal, Mohamad Ezrien; Md Salleh, Mohd Fairuz; Ahmad, Azlina (2017)
This paper examines whether corporate governance compliance differs between earning and non-earning manipulating firms and the area of compliance deficiency in view of an improvement in corporate governance codes of best practices. Governance compliance was measured using corporate governance index based on 'ASEAN Corporate Governance Scorecard' (ACGSC). Samples of earnings manipulating firms were identified using the M-score model, matched against non-earnings manipulating firms by year and sector classification within 2012 and 2013, subsequent to issuance of ACGSC and Malaysian Codes of Corporate Governance 2012 (MCCG 2012). Differences in corporate governance compliance were analysed using 'independent samples t-test', 'Wilcoxon Mann-Whitney test', and 'Chi-Square test'. The result revealed "corporate governance compliance in aggregate", and specific governance areas of "stakeholders' whistleblowing and protection", "timely release of quality annual report", and "boards' appointment and remuneration criteria" were significantly different between earning and non-earning manipulating firms. Furthermore earning manipulating firms tend to have deficient governance compliance compared to opposite. This study implicates firms to adopt full compliance of corporate governance codes mainly in areas of "stakeholders' whistleblowing and protection", "timely release of quality annual report", and "board members appointment and remuneration criteria" to overcome potential earnings manipulation scheme.